Tissue-specific localization of polyketide synthase and other associated genes in the lichen, Cladonia rangiferina, using laser microdissection - Elshobary, Mostafa E.; Becker, Michael G.; Kalichuk, Jenna L.; Chan, Ainsley C.; Belmonte, Mark F.; Piercey-Normore, Michele D. (Zenodo, 2018)
Elshobary, Mostafa E., Becker, Michael G., Kalichuk, Jenna L., Chan, Ainsley C., Belmonte, Mark F., Piercey-Normore, Michele D. (2018): Tissue-specific localization of polyketide synthase and other associated genes in the lichen, Cladonia rangiferina, using laser microdissection. Phytochemistry 156: 142-150, DOI:10.1016/j.phytochem.2018.09.011, URL: http://dx.doi.org/10.1016/j.phytochem.2018.09.011